Marketing / Eric N. Berkowitz, Roger A. Kerin, Steven W. Hartley, William M. Rudelius - Berkowitz, Eric N. [et.al] (1994)
Marketing a focus on the consumer, marketing in the organization, an overview, the changing marketing enviroment, ethics and social responsibility in marketing, global markets and cross, cultural analysis, consumer behavior, organizatinal markets and buyerbehavior, collecting and using marketing information, market segmentation, targeting, and posistioning, relationship marketing, information technology, and forecasting, development new product, managing the product, pricing, relationg objetives to revenues and costs, arriving at the final price, marketing channels and wholesaling, physical distribution and logistics management, retailing, promotional process, sales promotion, and publicity, advertising, personal selling and sales management, the strategic marketing process, the planning phase, the strategic marketing process, implementationa and control phases, international marketing, marketing of services.